Principles for socially inclusive digital tools for smallholder farmers: A guide - Dittmer, Kyle M.; Burns, Sessie A.; Shelton, Sadie W.; Wollenberg, Eva Karoline (2022)
The digital ecosystem and its actors have increasing influence over how food is produced, what food people buy, and the flow of information among farmers, supply chain actors, and consumers. Efforts to transform food systems towards sustainability, including climate change resilience and mitigation, similarly rely on digital resources and offer the opportunity to scale up best practices rapidly at low cost. Yet the top-down and often public good or corporate-driven nature of digital tools can be at odds with the ethos of farmers’ self-determination and empowerment, especially for smallholder farmers in low- and middle-income countries (LMICs). This guide seeks to address concerns with the current digitalization of food systems with a set of principles to instruct development and implementation of socially inclusive digital tools with smallholder farmers. The principles are intended to increase social and livelihood benefits of digital tools for diverse and underrepresented groups of farmers. The co-creation of farm practices with farmers is framed as an element of social inclusion that ensures relevance to farmers’ livelihoods and development of robust technical solutions. The principles aim to support digital developers and managers using digital tools with farmers and help funders, farmers’ organizations or nongovernmental organizations (NGOs) hold tool developers or managers accountable to social inclusion principles.